Overview of Stress Levels of Anesthesiology Nursing Study Program Students in Preparing Final Projects at Harapan Bangsa University - Putriana Bainjap; Danang Tri Yudono; Amin Susanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Stress is a common psychological condition that can be experienced by anyone, including students who are preparing their final assignments. Stress in students can be influenced by various internal factors such as the individual's ability to manage time and pressure, as well as external factors such as academic demands and social support. Its impact is very significant on mental health, learning motivation, and the quality of final assignment completion. This study aims to determine the stress levels of students in the Anesthesiology Nursing Study Program at Harapan Bangsa University based on gender and age. The study used a quantitative descriptive method with a cross-sectional approach. The sample consisted of 169 students who were in the final assignment preparation stage. Stress levels were measured using a Guttman scale questionnaire consisting of 23 questions. The results showed that 74 respondents (43.79%) experienced moderate stress, 60 respondents (35.50%) experienced severe stress, 28 respondents (16.57%) experienced mild stress, and only 7 respondents (4.14%) experienced no stress. Based on gender, 20 male respondents (11.83%) experienced moderate stress, while 54 female respondents (31.95%) experienced moderate stress, and 49 (28.99%) experienced severe stress. In terms of age, respondents aged 21 and 22 both experienced moderate stress at 15.38%, while respondents aged 22 also experienced severe stress at 15.38%. Overall, student stress levels tended to be in the moderate to severe category, indicating the need for more systematic psychological attention and intervention.